PELAYANAN PERIZINAN BERUSAHA UMKM MELALUI SISTEM ONLLINE SINGLE SUBMISSION RISK BASED APPROACH (OSS-RBA) PADA DPMPTSP KABUPATEN KARIMUN - Silvi Permata Sari; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Licensing through OSS-RBA at the Investment Office and One-Stop Integrated Services of Karimun Regency aims to create a licensing process that is easy, fast and efficient for micro, small and medium enterprises in Karimun Regency. In the process of running licensing through OSS-RBA, there are several inhibiting factors, namely lack of socialization activities, there are still business licensing services that have not been registered in the OSS-RBA application, lack of public understanding or digital divide and unstable internet network. This study aims to determine UMKM Business Licensing Services through the Online Single Submission Risk Based Approach (OSS-RBA) System. The concept of the theory used is the theory of public service by Alanezi in Ningsih Ardila Sari 2021. By using descriptive qualitative research methods and data collection techniques based on interviews, observations and documentation. The results of the research that researchers got were that the implementation of UMKM business licensing services had gone quite well, but there were still several factors that became obstacles experienced by the Investment Office and One-Stop Integrated Services of Karimun Regency so that what was implemented was not effective. Keywords : Licensing, Public Services, Micro, Small and Medium Enterprises